Hybrid surface layers with antibacterial and anti-inflammatory activity for implants materials - Mariia A. Piatkova; Konstantine V. Nadaraia; Arina I. Ponomarenko; Igor V. Manzhulo; Mariia S. Gerasimenko; Arina I. Pleshkova; Evgeny A. Belov; Igor M. Imshinetskiy; Ksenia A. Fomenko; Ivan S. Osmushko; Aleksey G. Kozlov; Sergey V. Gnedenkov; et al. (Journal of Magnesium and Alloys)
Currently, there is an essential need for bioresorbable bone implants with antibacterial, anti-inflammatory properties as well as osteoinductivity. Considering this, in presented study for the first time hybrid Mg-ZK coatings with polydopamine (PDA), menaquinone-7 (MK-7), zoledronate (ZA) and vancomycin on the hydroxyapatite (HA) containing layer are formed. Porous coatings were obtained by the plasma electrolytic oxidation (PEO) on an Mg alloy, then MK-7 was impregnated into the pores and PDA film with ZA and vancomycin was polymerized on the samples surface. The presence of HA and organic bioactive compounds was confirmed by EDS, Raman spectroscopy, XRD and XPS. Surface free energy values of hybrid coatings are close to optimal for cell adhesion: 75.28 ± 1.35 mJ/m2. Viability tests of the medium, in which Mg-ZK implants were soaked, revealed cytotoxic activity on human osteosarcoma cells with no such an effect on fibroblasts. Antibacterial tests showed an inhibition zone on S. aureus with no viable colonies on the hybrid coatings. The growth inhibition zones for the samples with the hybrid coating were 21 ± 1 mm. Data of electrochemical impedance spectroscopy shows increase of corrosion resistance of samples with hybrid coating by 7 times comparing the Mg alloy without a coating. These properties make the hybrid Mg-ZK coating an attractive modification for bone implants.